Pengaruh Penggunaan Media Audio Visual dalam Mata Pelajaran Aqidah Akhlak terhadap Minat Belajar Siswa Kelas VIII MTs Muhammadiyah Tawangsari - Dawam Masykur Rizqo; Muhammad Kurniawan Budi Wibowo; Ngatmin Abbas (At Turots: Jurnal Pendidikan Islam, 2025)
This study aims to determine how the application of audio-visual media by teachers in learning Aqidah Akhlak subjects and how much influence the media has on the learning interest of class VIII students of MTs Muhammadiyah Tawangsari in the 2024/2025 school year. This research uses a quantitative approach with a quasi-experimental method. The research sample amounted to 28 students taken from four classes using proportional sampling technique. The main instrument in data collection is a questionnaire that has been tested for validity and reliability. The results showed that the application of audio-visual media by teachers was in the moderate to good category, with 50% of respondents stating the use of media in the good category, 42.86% were sufficient, and only 7.14% stated that it was not good. The results of students' interest in learning showed 50% in the good category, 39.29% were sufficient, and 10.71% were not good. The simple regression test resulted in an R Square value of 0.012, which means that the effect of using audio-visual media on learning interest is only 1.2%, while the rest is influenced by other variables. This study concludes that the use of audio visual media contributes positively although at a very low level of influence on students' interest in learning. The implications of these findings emphasize the importance of teacher training in developing and implementing interesting learning media. Future research is recommended to expand the sample size, location coverage, and incorporate a qualitative approach to explore other factors that influence students' interest in learning.